Implementation of Final Income Tax on Savings Interest at Bank BRI KCP Tanjung Agung - Zulvina Syah Putri; Ratna Septiyanti (LPPM STIE Krakatau, 2026)
Taxes are one of the largest sources of revenue for the Indonesian state today. The purpose of writing this report is to find out the procedure for calculating the withholding of Income Tax (PPh) Article 4 paragraph (2) on savings interest at Bank BRI KCP Tanjung Agung. Tax withholding is carried out by 20% for balances above IDR 7,500,000 and 15% for balances below IDR 7,500,000. The analysis method used is descriptive to assess the suitability of the tax calculation with applicable regulations. The results of the study show that the calculation of savings interest uses the daily balance method and is carried out automatically by the bank system at the end of each month. Tax withholding has also been integrated into the banking system so that it is carried out automatically when interest is posted to the customer's account. Because Income Tax Article 4 paragraph (2) is final, customers do not need to report it again in the Annual Tax Return. Although savings interest taxes reduce the net return received by customers, this system provides administrative convenience and legal certainty for taxpayers. With the implementation of an automatic tax withholding system, the tax administration process in banks becomes more practical, accurate, and efficient for customers and banks. Therefore, the implementation of Income Tax Article 4 paragraph (2) on savings interest is expected to continue to increase taxpayer compliance while supporting the optimization of state revenue from the tax sector.